The interpretation and application of the principal purpose test in South Africa - Killoran, Robyn Lindsay (My University, 2021)
The introduction of the Principal Purpose Test (PPT) in the Multilateral Convention to Implement Tax Treaty Related Measures to Prevent Base Erosion and Profit Shifting (MLI) is widely regarded as the most significant change to international tax policy in the past 100 years. As a signatory to the MLI, South Africa has indicated that it intends to adopt the PPT. By examining the historical development of the PPT and the principles of statutory interpretation in South Africa, this report will analyse the PPT and consider how it is to be interpreted and applied in a South African context. The PPT's interaction with the South African domestic General Anti-avoidance Rule will be examined and whether the broad and vague provisions of the PPT align with the principle of legal certainty as enshrined in the Constitution
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Commerce (in Taxation), 2021
Keywords: UCTD; Multilateral Instrument; MLI; Principal Purpose Test; PPT; Treaty Shopping; SDG-8: Decent work and economic growth